Thomas Jefferson author of America - Hitchens, Christopher 1949-2011 (Atlas Books/HarperCollins, 2005)
Hitchens brings the character of Jefferson to life as a man of his time and also as a symbolic figure beyond it. Conflicted by power, Jefferson wrote the Declaration of Independence and acted as Minister to France yet yearned for a quieter career in the Virginia legislature. Predicting that slavery would shape the future of America's development, this professed proponent of emancipation continued to own human property. He negotiated the Louisiana Purchase with France, doubling the size of the nation, and authorized the Lewis and Clark expedition, opening up the American frontier. The Barbary War, a lesser-known chapter of his political career, led to the building of the U.S. Navy and the fortification of America's reputation regarding national defense. In the background is the fledgling nation's struggle for independence, formed in the crucible of the eighteenth-century Enlightenment, and, in its shadow, the deformation of that struggle in the excesses of the French Revolution. --From publisher description.
Hitchens brings the character of Jefferson to life as a man of his time and also as a symbolic figure beyond it. Conflicted by power, Jefferson wrote the Declaration of Independence and acted as Minister to France yet yearned for a quieter career in the Virginia legislature. Predicting that slavery would shape the future of America's development, this professed proponent of emancipation continued to own human property. He negotiated the Louisiana Purchase with France, doubling the size of the nation, and authorized the Lewis and Clark expedition, opening up the American frontier. The Barbary War, a lesser-known chapter of his political career, led to the building of the U.S. Navy and the fortification of America's reputation regarding national defense. In the background is the fledgling nation's struggle for independence, formed in the crucible of the eighteenth-century Enlightenment, and, in its shadow, the deformation of that struggle in the excesses of the French Revolution. --From publisher description.
Keywords: Jefferson, Thomas -- 1743-1826; Presidents -- United States -- Biography; Verenigde Staten; USA; Biografie